Diet in Patients with Acute Pancreatitis - Ye. Ye. Achkasov; N. M. Fedorovsky; A. V. Pugayev; S. V. Kalachyov (Общая реаниматология, 2008)
Objective: to define a role of various maintenance modes, such as enteral tube feeding (ETF) and complete parenteral feeding in different phases of acute pancreatitis (AP). Subjects and materials. The impact of various modes of nutritional support on pancreatic secretory activity and the course of AP was comparatively analyzed in 774 patients (mean age 45.3±4.7 years) with AP. The criteria for evaluation of the activities of the pancreas and its inflammatory process activity were considered to be clinical and laboratory parameters (pain, body temperature, hemogram, amylasemia, the degree of dynamic ileus and abdominal inflammatory infiltrate, and the level of gastrointestinal peptides), and ultrasonographic and computed tomographic data. The additional impact of different types of protein-calorie provision on pancreatic secretory activity was studied in 23 patients with external pancreatic fistulas, by using debetometry. Results. ETF was shown to have a stimulating effect on pancreatic secretion and AP worsening when it was used in the early phases of the disease. The optimum time of complete parenteral feeding (days 5—14 after the onset of the disease) and the criteria for the possible initiation of ETF were determined. Emphasis was laid on the important role of enteral feeding in a package of therapeutic measures in AP in the phase of pyonecrotic lesions. Conclusion. The proposed nutritional support tactics along with mini-invasive surgical treatments could reduce postoperative and overall mortality rates to 4.2 and 3.7%, respectively. Key words: acute pancreatitis, protein-calorie provision, nutritional support, enteral tube feeding, parenteral feeding, intestinal lavage, pancreatic secretion.